Curcuma mangga-mediated synthesis of gold nanoparticles and their photothermal and protein interaction studies / Foo Yiing Yee - Foo , Yiing Yee (2018)
Utilization of toxic chemicals in the synthesis of gold nanoparticles (AuNPs), poor stability and low biocompatibility of AuNPs in physiological system are some of the factors that limit the clinical applications of AuNPs. Herein, we describe the use of Curcuma mangga (CM) extract as an alternative method for the synthesis of safe, stable and biocompatible CM-AuNPs to circumvent these constraints. Effects of time, CM extract and gold (III) chloride trihydrate (HAuCl4·3H2O) concentration on the synthesis of CM-AuNPs were studied using UV-Vis spectroscopy. Incubation of 4 ml of CM extract (10 mg/ml) and 10 ml of HAuCl4 (1 mM) for 24 h at room temperature was found to produce spherical AuNPs with higher stability, thus these conditions were used to synthesize CM-AuNPs for subsequent studies. Transmission electron microscopic analyses characterized CM-AuNPs as spherical particles with an average particle diameter of 15.6 nm. The field effect scanning electron microscopic data also supported these results. Fourier transform infrared spectral analysis showed importance of carbonyl groups of terpenoids, present in the CM extract used in the synthesis of CM-AuNPs, which act as a reducing agent. Greater stability of CM-AuNPs compared to citrate-AuNPs in various buffers or media was evident from the absence of significant change in the UV-Vis spectral characteristics. CM-AuNPs also exhibited low cytotoxicity to human colon fibroblast, CCD-18Co and human lung fibroblast, MRC-5 cell lines. Furthermore, CM-AuNPs were also found to be red cell-compatible, showing less than 10% hemolysis without any erythrocytes’ aggregation. The interaction of CM-AuNPs with human serum albumin (HSA) was also investigated to understand their transport in human circulation. Fluorescence spectral studies suggested that the interaction of CM-AuNPs with HSA was initiated by dynamic quenching mechanism. The binding constant obtained at 25˚C was found to be 0.97 × 104 M-1, indicating moderate binding affinity between CM-AuNP and HSA. Thermodynamic analysis revealed involvement of hydrophobic forces in CM-AuNP-HSA complexation. Alteration in the tertiary structure of the protein was also observed upon interaction of HSA with CM-AuNPs, as analyzed by circular dichroism analysis. Three-dimensional fluorescence spectral results suggested microenvironmental perturbations around protein’s fluorophores upon CM-AuNPs interaction with HSA. CM-AuNPs binding site has been predicted to be Sudlow’s site II, located in subdomain IIIA of HSA. Photothermal efficiency of CM-AuNPs was evident from the increase in the media temperature upon photoirradiation. The media temperature increased with increasing laser intensity and CM-AuNP concentrations. The percentage viability of MCF-7 breast cancer cells was markedly reduced upon photothermal treatment with CM-AuNPs. CM-AuNP-dependent photothermal-induced MCF-7 cells’ death were found to be mediated by apoptosis. All these results suggested potential use of CM-AuNPs as therapeutic agents in cancer therapy.